2010
DOI: 10.1016/j.ajhg.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

GJC2 Missense Mutations Cause Human Lymphedema

Abstract: Lymphedema is the clinical manifestation of defects in lymphatic structure or function. Mutations identified in genes regulating lymphatic development result in inherited lymphedema. No mutations have yet been identified in genes mediating lymphatic function that result in inherited lymphedema. Survey microarray studies comparing lymphatic and blood endothelial cells identified expression of several connexins in lymphatic endothelial cells. Additionally, gap junctions are implicated in maintaining lymphatic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 29 publications
6
111
0
1
Order By: Relevance
“…Recently, two more genes (GJC2 and CCBE1) were identified to be causally associated with lymphedema. The GJC2 gene encodes connexin 47, an intercellular gap junction protein, and mutations in the protein were postulated to cause impaired gap junction activities and result in defective lymphatic flow (Ferrell et al 2010). CCBE1 has been shown to play a role in lymphatic sprouting during zebrafish development, and mutations in CCBE1 were found in patients with Hennekam lymphangiectasia -lymphedema syndrome (Alders et al 2009;Hogan et al 2009).…”
Section: Primary Lymphedemamentioning
confidence: 99%
“…Recently, two more genes (GJC2 and CCBE1) were identified to be causally associated with lymphedema. The GJC2 gene encodes connexin 47, an intercellular gap junction protein, and mutations in the protein were postulated to cause impaired gap junction activities and result in defective lymphatic flow (Ferrell et al 2010). CCBE1 has been shown to play a role in lymphatic sprouting during zebrafish development, and mutations in CCBE1 were found in patients with Hennekam lymphangiectasia -lymphedema syndrome (Alders et al 2009;Hogan et al 2009).…”
Section: Primary Lymphedemamentioning
confidence: 99%
“…The authors conclude that Cx26 seems to enhance metastasis, probably by promoting invasion of the lymphatic vessels. Very recently, mutations in GJC2 (Cx47), another member of the connexin family, have been reported to cause primary lymphedema in humans (Ferrell et al, 2010;Ostergaard et al, 2011). With this in mind, it appears promising to further analyze connexin protein expression and function during development and maintenance of the lymphatic vessel system in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that certain mutations in the human gap junction protein Cx47 can cause 2807 Cx26 in peripheral lymphangiogenesis inherited human lymphedema (Ferrell et al, 2010;Ostergaard et al, 2011). In this study we investigated the essential role of ectodermally expressed Cx26 for peripheral lymphangiogenesis in mice.…”
mentioning
confidence: 99%
“…43 Data suggest that coordinated function of gap junctions is needed to mediate the propagation of spontaneous contractions in the lymphatic vasculature. 44 Although these in vivo studies have demonstrated the effect of deletion of connexin, it is still unknown if the changes in expression of connexin seen in chronic wounds affect lymphangiogenesis.…”
Section: Cellular Component In Dfu and Lymphedemamentioning
confidence: 99%